2020
DOI: 10.1042/bsr20201495
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a novel cholesterol efflux assay using immobilized liposome-bound gel beads with the conventional method

Abstract: Cholesterol efflux capacity (CEC) is an atheroprotective function of high-density lipoprotein (HDL). CEC is currently measured using artificially prepared foam cells composed of cultured macrophage and 3H-cholesterol. However, this conventional method is not suitable for clinical laboratory use due to poor repeatability, complexity, and low safety. Recently, we reported a novel CEC assay, called the immobilized liposome-bound gel beads (ILG) method. The ILG method is an alternative to foam cells, comprised of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…In the ILG method, it is known that globulin has the ability to efflux cholesterol [ 15 ]. In addition, previous reports have described the effect of serum proteins, especially albumin, on CEC obtained using BDS as the cholesterol acceptor [ 16 , 20 , 21 ]. Hence, these serum proteins might have extracted cholesterol from the ILM, and this deviation may have occurred.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the ILG method, it is known that globulin has the ability to efflux cholesterol [ 15 ]. In addition, previous reports have described the effect of serum proteins, especially albumin, on CEC obtained using BDS as the cholesterol acceptor [ 16 , 20 , 21 ]. Hence, these serum proteins might have extracted cholesterol from the ILM, and this deviation may have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…As for the relationship between beads-based methods (the ILG and ILM methods) and the conventional cell-based method, the ILM method does not involve transporter-mediated efflux, which is reflected in cellular methods. However, it has already been reported that the CEC of the conventional cellular method is well correlated with the ILG method, and CEC values of BDS reflect the HDL-CEC [ 15 , 16 ]. Moreover, when CEC values obtained by the ILG and conventional methods were compared between HDL 2 and HDL 3 , similar trends (HDL 2 > HDL 3 ) in both methods were observed, which suggested that the specificities of the ILG method and cell-based method to HDL were similar, whereas the ILG method showed different behavior in CEC values of apolipoprotein E-containing HDL and free apoA-I from the cell-based method: CEC values by the ILG method were quite lower than those by the cell-based method [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CEC assay, however, is a tedious cell-based assay that typically uses radiolabeled cholesterol and is, therefore, not suitable for routine diagnostic testing. The fact that the AER assay and other recently developed cell-free surrogate assays for HDL function 13,20,21 also closely correlate with the CEC assay and ASCVD events, it may be possible to develop one of these newer fluorescent and potentially automatable assays into a routine diagnostic test. Like the well-known aphorism says, if one waits long enough, even bad things can sometimes turn good.…”
Section: Dasseux and Remaleymentioning
confidence: 99%